2008
DOI: 10.1136/gut.2007.146258
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced susceptibility to pancreatitis in severe hypertriglyceridaemic lipoprotein lipase-deficient mice and agonist-like function of pancreatic lipase in pancreatic cells

Abstract: LPL-deficient mice with severe hypertriglyceridaemia display enhanced susceptibility to acute pancreatitis. High levels of chylomicrons and free fatty acids result in pancreatic cell injury. Pancreatic lipase has a dual effect: generating free fatty acids from chylomicrons and preventing Ca(2+) overload in pancreatic acinar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 33 publications
3
52
1
Order By: Relevance
“…Although it has been known for 40 years that cytosolic Ca 2+ signals in pancreatic acinar cells are initiated by release from internal stores (5), it has also been recognized for a long time that following the initial release from the intracellular stores there is an important Ca 2+ entry phase that is essential for refilling the stores and indeed for stimulant-evoked enzyme secretion (48)(49)(50). Previous investigations have demonstrated that the most important mediators of acinar cell damage, namely alcohol, fatty acids, fatty acid ethyl esters, and bile acids all primarily release Ca 2+ from various internal stores (28,29,37,42,43,51), but that this initial phase is followed by store-operated Ca 2+ entry, which plays a crucial role in the destruction of the cells (2,4,5,10). Our electrophysiological data (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been known for 40 years that cytosolic Ca 2+ signals in pancreatic acinar cells are initiated by release from internal stores (5), it has also been recognized for a long time that following the initial release from the intracellular stores there is an important Ca 2+ entry phase that is essential for refilling the stores and indeed for stimulant-evoked enzyme secretion (48)(49)(50). Previous investigations have demonstrated that the most important mediators of acinar cell damage, namely alcohol, fatty acids, fatty acid ethyl esters, and bile acids all primarily release Ca 2+ from various internal stores (28,29,37,42,43,51), but that this initial phase is followed by store-operated Ca 2+ entry, which plays a crucial role in the destruction of the cells (2,4,5,10). Our electrophysiological data (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3D). (42,43), but in combination-as fatty acid ethyl esters-they are much more powerful Ca 2+ releasers (37) (28). Fig.…”
Section: Concentration Dependence Of the Acute Effects Of Gsk-7975a Omentioning
confidence: 99%
“…Recent work has shown that palmitoleic acid ethyl ester (POAEE) releases Ca 2+ from both the endoplasmic reticulum (ER) and an acid store in the apical part of pancreatic acinar cells and indicates that it is the release from the acid store, predominantly through IP 3 receptors (IP 3 Rs) of types 2 and 3, that is principally responsible for the intracellular activation of trypsinogen (12). Long-chain fatty acids, for example palmitoleic acid, can induce a more slowly developing Ca 2+ release also causing intracellular trypsinogen activation (10,13,14), which to a large extent depends on inhibition of mitochondrial function and subsequent reduction in the capacity to remove excess Ca 2+ from the cytosol through ATP-dependent Ca 2+ pumps (10,15).…”
mentioning
confidence: 99%
“…Hypertriglyceridemia is also a recognized cause of pancreatitis (10) and the presence of high concentrations of fatty acid ethyl esters [FAEEs, non-oxidative products of alcohol and fatty acids (FAs)], particularly in the pancreas, was reported in a postmortem study of subjects intoxicated by alcohol at the time of death (11). FAEEs induce trypsin activation and vacuole formation (12) and also elicit global sustained [Ca 2ϩ ] i elevations, due to emptying of intracellular Ca 2ϩ stores, causing Ca 2ϩ -dependent necrosis (9,13,14).…”
mentioning
confidence: 99%